Monetizing 5G Capabilities: A Socio-Economic Perspective - Asma Chiha; Sofie Verbrugge; Didier Colle (International Telecommunications Society (ITS), 2025)
Mobile Network Operators continue to face challenges in generating sufficient revenue streams from 5G networks, especially in use cases where societal value far exceeds immediate financial returns. Safety-critical applications, such as real-time emergency response, autonomous vehicle coordination, and drone-based emergency services, demonstrate unique capabilities of 5G in delivering ultra-low latency and high reliability. However, these applications often struggle to justify network investment purely on commercial grounds. This research argues for a broader, impact-driven perspective that recognizes the socio-economic and environmental value these solutions deliver, particularly in alignment with global sustainability goals. Focusing on Belgium, this study investigates the deployment of a 5G-based Safety Drone Shield solution designed to support emergency services with real-time situational awareness through drones equipped with advanced imaging, sensors, and ultra-reliable connectivity via 5G networks. We adopt a hybrid socio-economic assessment framework, combining qualitative tools (interviews and surveys) with quantitative methods including Social Return on Investment (SROI) and sensitivity analysis. This enables us to evaluate both tangible and intangible impacts in a rigorous and structured way. Our findings show that the 5G Safety Drone solution generates up to exteuro28 of societal value per exteuro1 invested, which means an SROI ratio of 28:1. Positive impacts are particularly pronounced in relation to the UN Sustainable Development Goals (SDGs), notably Goal 3 (Good Health and Well-being), Goal 9 (Industry, Innovation and Infrastructure), and Goal 11 (Sustainable Cities and Communities).
Keywords: 330; 5G networks; socio-economic assessment; SDG; drone; emergency services; SROI